PERDAGANGAN LIMBAH B3 DALAM KONTEKS PERDAGANGAN BEBAS DIHUBUNGKAN DENGAN ASPEK PENEGAKAN HUKUM LINGKUNGAN INTERNASIONAL DAN IMPLIKASINYA TERHADAP KEPENTINGAN INDONESIA - Sumartini, Siti; Alam, Kodrat (Yustitia, 2015)
The Transboundary Movement Of Hazardous Wastes are pollutant that can be sold between state in international regime. The trade and environment debate conceals the conflictive relationship between two legitimate interests of the international community; the international protection of the environment1 and the liberalization of international trade. In other words, States must work together in order to further develop the law of sustainable development, especially that related environmental law enforcement. Indonesia as developing country must be protect of internasional trade